Efficient implementation of low cost and secure framework with firmware updates - Ines Ben Hlima; Halim Kacem; Ali Gharsallah (IET Computers & Digital Techniques)
Abstract Recently, the Internet of things (IoT) has become extensively used in our daily lives. This technology offers a new vision of the future internet where devices are interconnected and can communicate together. A big number of these devices complicates the firmware update and makes it more expensive since each node must be updated locally. Nevertheless, there are many cases where devices cannot change their location to upgrade the firmware locally due to an unreachable location or dangerous place. Therefore, it is necessary to remotely update the firmware of devices. In this study, the authors propose an efficient implementation of a low cost and secure framework of upgrading the firmware employing the latter On‐The‐Air programming technique. The authors present a proof of concept for a ubiquitous system applying wireless programmer. Our design offers a remote broadcasting of image code without disturbing the main functionality of nodes. The authors validated the performance of our design on a real network based on STM32 micro‐controllers. The results showed the reduction of the network time‐off, enabling a continuous operation of the ecosystem.